Factores decisivos para a escolha do binómio curso/instituição: o caso do ensino superior agrário português - Isabel Ribeiro (Universidade do Minho, 2008)
To identify factors that are critical in the decision making about institution and course is the main objective of this work and it leans on in primary data obtained through the application of an inquiry to the students' universe that enrolled, for the first time, during 2003/2004, in courses of agricultural sciences (909 Students). Regarding the decision choice about the education, the estimation results identified as determinant factors: personal factors like culture and values and the fact of the individual to be informed about courses and institutions that he can frequent; academic performance factors, namely, access note, reasons to the higher education application, and attitudes about work and study; contextual factors , particularly, the fact that the individual does not live with his parents, the subsistence means, the not specific preparation that the course provides, the prestige of the course, the family tradition, the existence of larger supply, and the major probability of entering in the degree course and in the institution; and, finally, social and economics factors as income level and the level of the progenitors' education.